Free convection heat transfer along a variable wall temperature vertical cylinder - Abdul Sufi Noordin (2015)
This report serves as a numerical analysis and literature review for free convection heat transfer along a cylinder, which is vertical and possessing a wall temperature, proportional to xn. x is the distance measured from cylinder’s base or its leading edge, and nx is a constant. J.J. Shu and I. Pop were the first to discuss and model the governing equations. Thus, this reports serves as a continuation to their study. Numerous studies with different parameters were conducted to analyze free convection along an upright cylinder, which is isothermal, as well as one, which has a variable surface temperature. However, none presented a direct comparison of the effect of these two different surface conditions. Thus, this paper will present and compare this difference. Firstly, extensive research on previous work in relation with the study were done and analyzed. Following that, a detailed analysis on the numerical solutions was constructed and presented. The numerical computations will be obtained with the implementation of ‘MATLAB’, a multi-paradigm numerical computing environment. Solutions, including the temperature and velocity profile plots, together with the rate of heat transfer plot, will be presented at both the base of the cylinder, which has the stretched stream wise coordinate xi=0, and the asymptotically solution far downstream, where xi → ∞. In addition, the effect of parameters such as n and Prandtl number, Pr, will be studied. Finally, a conclusion will be drawn regarding the significance of these parameters and the relevancy of the governing equation.